Hubungan Pola Asuh Orang Tua Dengan Kejadian Temper Tantrum Pada Usia Toddler Di Dukuh Pelem Kelurahan Baturetno Banguntapan Bantul - Nisaus Zakiyah (Poltekkes Kemenkes Surakarta, 2017)
Abstract: parenting style, temper tantrum, toddler. Age of1-3 years old is the age which is easy to get temper tantrum. The children are not able yet to express their wants and needs clearly. The effect of temper tantrum could be dangerous for example the child could be rolling on the floor and could hurt himself. The purpose of the study was to investigate the relationship between parents’ parenting styles and temper tantrum cases on toddlers in Pelem Baturetno Banguntapan Bantul in 2015. The study employed survey analytic research with cross-sectional approach. The samples were 41 respondents taken through total sampling technique. The data were analyzed by using Pearson product moment. Parents’ parenting style tends to be poor such as let the child crying, rarely make complement, compare children, shout, and never ask children’s opinion. Meanwhile, the temper tantrum frequently happen are whining, crying, and screaming. The significance value of Pearson Product Moment is 0.027 (p < 0.05). It means that there is a relationship between parents’ parenting style with temper tantrum on toddlers with a correlation value of 0.344 which shows low relation. There is a relationship between parenting style with temper tantrum case on a toddler in Pelem Baturetno Banguntapan Bantul in 2015. Parents are expected to give parenting with love, to create normal rules, to be consistent, to give responsibility, to be role models, and to give complement so that those can reduce the temper tantrum.